Faktor-Faktor Yang Mempengaruhi Kinerja Karyawan Dalam Perspektif Manajemen Sumber Daya Manusia Islami Pada CV. Ono Trans Sejahtera - Windari, Fitri; Nasution, Yenni Samri Juliati; Harahap, Rahmat Daim (CV. ITTC INDONESIA, 2023)
This study aims to examine the factors that influence employee performance in the perspective of Islamic human resource management on CV. Ono Trans Sejahtera either partially or simultaneously. This study used quantitative methods with data collection using Likert scale method. The subjects used in this study were CV employees. Ono Trans Sejahtera totaled 35 people and was taken using total sampling. Data analysis techniques through IBM SPSS statistical program 25. The results of this study show that Hypothesis one, wages have a positive and significant effect on employee performance with a significant value of 0.029 ˂ 0.05. Hypothesis two, work motivation has a positive and significant effect on employee performance with a significant value of 0.025 ˂ 0.05. Hypothesis three, work discipline has a positive and significant effect on employee performance with a significant value of 0.009 ˂ 0.05. Hypothesis four, the work environment has a positive and significant effect on employee performance with a significant value of 0.000 ˂ 0.05. And Fifth, simultaneously the variables of wages, work motivation, work discipline, and work environment have a positive and significant effect on employee performance with a significant value of 0.000 ˂ 0.05. With a Coefficient of Determination of 93.4%. So from the results of the study, overall in partial and simultaneous trials stated that it was influential and significant.